Creative destruction [car crash testing]. - Blau, J.
Crashing cars-lots of them-is how Volvo safety engineer Daniel Hedqvist earns his living. Running cars into steel barriers or other cars or the sides of mountains is his job. These days the Swede rigging up plenty of Fords for crash tests. Ford owns the prestigious Volvo, Jaguar, and Aston Martin car companies, and has made Sweden its center of excellence for vehicle safety testing. There's a good reason why the second-largest US car maker has ceded this area of expertise to a non-US supplier: few auto companies have won as many awards for car safety as Volvo. This article discusses safety testing of cars at Volvo using virtual crashes and real crashes. The unique features of the test facilities are briefly outlined including the two intersecting test tracks: a 154-meter fixed track and an 80-meter movable one that can be turned as much as 90 degrees. Front and side collisions can thus be tested at virtually all angles. If the back door at the end of the movable track is opened, cars can be sent flying directly into the rocky hillside outside. For so-called barrier tests, a single car on the fixed track hurtles into an 850-ton block at the far end.
Keywords: Aston Martin; Ford; Jaguar; Sweden; Volvo; Car crash testing; Front collisions; Intersecting test tracks; Mountain side; Safety testing; Side collisions; Steel barriers; Virtual crashes